DSC studies on crystallization mechanisms of tellurite glasses - Yukimitu, K.; Oliveira, R. C.; Araujo, E. B.; Moraes, João Carlos Silos [UNESP]; Avanci, L. H. (Elsevier B.V., 2005)
The purpose of this work is to study the 20Li(2)O-80TeO(2) glass using the differential scanning calorimetry (DSC) and X-ray diffraction (XRD) techniques in order to understand the crystallization kinetics on this glass matrix. To study the glass by DSC, screened samples with different particle sizes to resolve the observed asymmetrical crystallization peak were used. DSC curves for particles smaller than 38 mum in size show two distinct crystallization peaks, associated to distinct phase transformation in this glass, leading to activation energies at 301 and 488 kJ mol(-1). XRD analysis reveals that the first crystallization peak is attributed to TeO2 crystalline phase while the second one to the alpha-TeO3 and an unidentified phase.(C) 2004 Elsevier B.V. All rights reserved.
Keywords: DSC; crystallization mechanism; tellurite glasses